Islamic Education Learning Process for Hyperactive Children in Class IIB SD UNP Laboratory - Rahayu, Sri; Rahman, Rini (EDUMALSYS Journal of Research in Education Management, 2023)
This research is motivated by the phenomenon of children with special needs who can learn together with other normal children in the learning process which are called inclusive schools. The purpose of this study was to find out the PAI learning process for hyperactive children at the UNP Laboratory Development Elementary School, including (1) The method used by the teacher in the PAI learning process. (2) Assessment of learning outcomes for hyperactive children. (3) The behavior of hyperactive children and the teacher's efforts to overcome them. This study used a qualitative research method with a descriptive approach. Data collection techniques are carried out by observation, interviews, and documentation. Sources of information in interview techniques are Islamic Religious Education teachers, class teachers, and accompanying teachers for hyperactive children in class IIB UNP Laboratory Development Elementary School. The results showed that: (1) The methods used by PAI teachers in learning were lecture, demonstration, and question and answer methods (2) Assessment of learning outcomes used written test instruments and oral tests. (3) Hyperactive children in class IIB show several behaviors during the learning process. Hyperactive children are not focused, like to scribble on the table, draw, play with objects around them, and cannot sit still. In this case, PAI teachers, class teachers, and accompanying teachers try to overcome each other.